Political-pedagogical foundations of the BNCC: considerations about the educational State and the production of hegemony (Revista de Estudios Teóricos y Epistemológicos en Política Educativa, 2021)
This article aims to carry out a theoretical analysis of the political-pedagogical characteristics of the Common Core State Standards (in Brazil, Base Nacional Comum Curricular – BNCC), as an expression of the State as a mediator of hegemonic relations in the Brazilian context. Methodologically, this work is structured from the dialectical historical materialism, based on the theoretical conception of Antonio Gramsci, which understands the State as a complex organism and technically, ethically and intellectually attached to hegemonic rationality. The work indicates that the BNCC, as a tool of political intervention, therefore pedagogical of the State, both focuses on the processes of building consensus with marked fidelity to hegemonic sociability and seeks to directly discipline educational practice, which means to focus on the very intentions of the educational community, consequently in the control and disciplining of the forces that indicate paths for the construction of experiences of sociability other than the hegemonic one.Keywords: Education policy. Curriculum policy. Common Core State Standards.